Pedestrian Guiding Signs Optimization for Airport Terminal - Jianxin Lin; Rui Song; Jifeng Dai; Pengpeng Jiao (Discrete Dynamics in Nature and Society)
The pedestrian guiding sign (PGS) is used to lead people within the transportation terminal to their directions efficiently and without boundaries. In this paper, we aim to optimize the guiding signs for people in the comprehensive transportation terminal with a mathematical model, which describes the pedestrian's reaction, judgment, and perception of the outline about the guiding signs, as well as pedestrian's moving status through self-organized characteristic behavior. Furthermore, the model also reflects the information intensity of the guiding signs within the pedestrian's visual field which is taken as the influence level score of PGS. In order to solve the model, cellular automation (CA) is employed to simulate the characteristics of the pedestrians such as crowd moving and sign selection.